Collaboration Principles between Telecommunication Operators and Over-The-Top (OTT) Platform Providers in the Context of the Indonesian Job Creation Regulation - Ramli, Ahmad M.; Ramli, Tasya Safiranita; Ramadayanti, Ega; Lestari , Maudy Andreana; Fauzi, Rizki (Journal of Telecommunications and the Digital Economy, 2022)
As anticipated, the existence of telecommunication regulations has become the focus of public attention as it can provide various protections. Further, the Indonesian Job Creation Law has provided new implications for the telecommunications operators in the form of Government support. Based on the principles of fairness, impartiality and non-discrimination, as well as maintaining service quality, it is expected that the telecommunications operator system in Indonesia will be able to develop and provide the best facilities in keeping with community needs. This has also opened up opportunities for the implementation of a new pattern of cooperation with the Over-The-Top (OTT) service that has been growing in popularity. This study applies a normative research method with online data collection techniques and seeks to produce an analysis, socialization and education with regards to the emergence of telecommunications operations principles, as well as the implementation of these principles in the Job Creation Law and its Implementing Regulations.